2014
DOI: 10.1186/1471-2261-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Can cardiac computed tomography predict cardiovascular events in asymptomatic type-2 diabetics?: results of a long term follow-up

Abstract: BackgroundDoubts remain about atherosclerotic disease and risk stratification of asymptomatic type-2 diabetic patients (T2DP). This study aims to evaluate the usefulness of calcium score (CS) and coronary computed tomography (CT) angiography (CTA) to predict fatal and non fatal cardiovascular events (CVEV) in T2DP.MethodsEighty-five consecutive T2DP undergoing CT (Phillips Brilliance, 16-slice) with CS and CTA were prospectively enrolled in a transversal case-control study. Patients were followed for 48 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…With regard to CAC, several studies in patients with type 2 diabetes have demonstrated CAC to be a useful risk marker for CVD events and mortality [ 15 , 27 31 ]. An extensive high CAC (>600) has been shown to be related to high risk of developing chronic CAD-related events; whereas acute CAD-related events mainly occurred in subjects with mild and moderate CAC score (1–600) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to CAC, several studies in patients with type 2 diabetes have demonstrated CAC to be a useful risk marker for CVD events and mortality [ 15 , 27 31 ]. An extensive high CAC (>600) has been shown to be related to high risk of developing chronic CAD-related events; whereas acute CAD-related events mainly occurred in subjects with mild and moderate CAC score (1–600) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also Faustino et al investigated the prognostic value of coronary CTA for cardiovascular events in 85 asymptomatic patients with DM type 2. 24 Cardiovascular events occurred in 10 (11.8%) patients after median follow-up of 48 (IQR 18-68) months: cardiovascular death in 2 (2.4%) patients, unstable angina in 1 (1.2%) patients, stroke 7 (8.4%) in patients. In the multivariate analyses, corrected for univariate significant variables, the absence of obstructive CAD (≥50%) was independently protective of events.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies assessed the prognostic value of coronary CTA in diabetic patients without chest pain syndrome. 15 , 22 , 24 From the CONFIRM (coronary CT angiography evaluation for clinical outcomes: an international multicentre) registry of 27,125 patients, Min et al selected 400 asymptomatic diabetic patients who underwent coronary CTA. 15 The prognostic value of CTA was investigated using the same composite endpoint as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these features are associated with a higher likelihood of near-term major adverse cardiovascular events. Several studies have shown the prognostic value of CCTA findings in subjects with asymptomatic DM 31 , 32 . Whether clinical outcomes can be impacted by CCTA screening, however, was only recently reported by the FACTOR-64 randomized clinical trial, which enrolled 900 asymptomatic patients with diabetes; while showing a 20% reduced risk of subsequent adverse cardiovascular events in those screened with CCTA, the findings were not statistically significant and this was due in part to the fairly low event rates 33 .…”
Section: Key Screening Methods For Detecting Subclinical Cardiovasculmentioning
confidence: 99%